Tinjauan Literatur Implementasi Asesmen dalam Kurikulum Merdeka: Penelitian - Ramalia, Arisa; S. Syamsurizal (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Merdeka Curriculum is an educational innovation implemented to overcome learning losses due to the Covid-19 pandemic and adapt to 21st century educational needs. In its implementation, assessment is a crucial element to support the planning and implementation of learning activities that suit student needs. This study examines five articles on the assessment of the Merdeka Curriculum published between 2023 and 2024. The study results show that assessment in the Merdeka Curriculum includes diagnostic, formative, summative, and authentic assessments. However, there are still various barriers to implementation, such as teachers' lack of understanding of the concept of authentic assessment, limited facilities, little training, and low use of assessment results as a basis for improving the learning process. With the support of government policies, continuous training, and collaboration between teachers, the implementation of assessment in the Merdeka Curriculum is expected to take place optimally to improve the quality of learning in schools.